Analisis Implementasi Supervisi Akademik Sebagai Upaya Peningkatan Profesionalisme Guru Agama (Studi Kasus di MTsN Kabupaten Brebes dan SMP Al Irsyad Tegal) - Abdul Majid Khon; Neli Rahmaniah (UMSU, 2018)
The aims of this research are to find out; (1) the urgency of academic supervision at SMP Al-Irsyad Tegal and MTsN Brebes, Jawa Tengah; (2) the picture of the academic supervision implementation, obstacles, and solutions; (3) the positive impact of the implementation of academic supervision in developing teacher of religion professionalism in SMP Al-Irsyad Tegal and MTsN Kabupaten Brebes, Jawa Tengah. The result showed that: (1) Academic supervision is necessary to do by a supervisor, in this case, the headmaster SMP Al-Irsyad Tegal and MTsN Brebes, which had done supervision activity so school activities can be directed to achieve the expected education purposes. (2) The implementation of educators supervision either at SMP Al-Irsyad Tegal or MTsN Model Brebes could be reviewed in some aspects, those are the purpose of supervision, the function of supervision, the types and technique of the implementation of supervision used. As for the steps had done, it included planning, implementing, and evaluating of supervision. Meanwhile, the obstacles in the implementation of supervision were a complexity of the headmaster’s duty as the leader, lack of preparation of supervised teachers and sometimes happens at the same time with other activities, such as training, workshop, etc. The effort made was by coordinating with senior teachers. (3) The positive impact of the implementation of academic supervision is motivating supervised teachers of the importance to improve competence, so the quality of the learners will increase, and then it shows more of a professional teacher.